11. Kebijakan Indonesia Belum Meratifikasi Statuta Roma 1998 - Maruf, Wakhid Aprizal; Putranti, Ika Riswanti; Rosyidin, Mohamad (Journal of International Relations, 2017)
Post WW-II world eyewitnessed one of the darkest age of humanity. Numerous bloodbaths of innocents occurred as forms of tyranny legitimation. Cambodia, Rwanda, and Yugoslavia were three of the abundant infamous degradations of humanity at the 2nd semester of the 20th century. However, under the universal spirit of humanity, international society reacted actively against those inhumane actions ergo UN formed ad hoc tribunal such as ICTY or ICTR. Yet those ad hoc tribunal were considered ineffective ergo the escalation of permanent court demands. This resulted in the birth of Rome Statute of the International Criminal Court. Rome Statute was positively acclaimed by international society and currently had been ratified by 124 countries. Still, Indonesia were not among them. This thesis would examine Indonesia’s policy of Rome Statute. Through constructivist perspective, this thesis would unfold norms disparities between international norms of Rome Statute and domestic norms of Indonesia. The perception of norms disparity would lead Indonesia to create a congruence of its norms ergo the policy to not ratify Rome Statute yet. To put the finger on the answer, this thesis would also encompass institutional dynamics of ICC and Indonesia’s commitment on Rome Statute, both explicit and implied commitments, started from Megawati’s, SBY’s, to Jokowi’s rule. As the result, it would be concluded whether there is norms disparity as the factor behind Indonesia’s policy to not ratify Rome Statute.